Islam sebagai Ideologi Alternatif di Abad ke Dua Puluh Satu - Muhammadiyah Dja'far (UIN Maulana Malik Ibrahim Malang, 1999)
Islam is the only divine religion that is passed down to all humanity, regardless of nationality, color, language, origin, and age. Islam is a message that contains the meaning of natural mission. Nature is a sentence that has a deep, beautiful, and great meaning. The existence of a natural Islam, showing without doubt to the universality of this treatise, and its flexibility, and its absolute ability to understand all the changing times, and the development of life, as well as the human view of itself in this life in all circumstances and conditions. The mission of Islam is capable of making breakthroughs and spreads in every time and place, for he is the only religion that carries the seeds of the ultimate and noble life for mankind. Indeed Islam is the religion of human nature and in fact faith is the milestone of Islamic life. It is therefore impossible to erect the palace of true Islamic life unless it is sustained above the milestone of acknowledgment of monotheism, for it is the essential acknowledgment for man to color his life, in accordance with God's will for him. Islam adalah satu-satunya agama samawi yang diturunkan ke segenap umat manusia, tanpa memandang jenis kebangsaan, warna kulit, bahasa, asal-usul, dan zamannya. Islam adalah risalah yang bermuatan makna misi alamiah. Alamiah adalah suatu kalimat yang mempunyai arti yang dalam, indah, dan agung. Adanya Islam yang alamiah, menunjukkan tanpa keraguan kepada kesemestaan risalah ini, dan fleksibilitasnya, serta kemampuannya yang mutlak memahami segala perubahan zaman, dan perkembangan kehidupan, maupun pandangan manusia itu sendiri terhadap kehidupan ini dalam segala situasi dan kondisinya. Misi Islam mampu melakukan terobosan dan tersebar dalam setiap waktu dan tempat, karena dia adalah satu-satunya agama yang membawa benih-benih kehidupan hakiki dan mulia bagi umat manusia. Sesungguhnya Islam adalah agama fitrah kemanusiaan dan sesungguhnya iman adalah tonggak kehidupan Islam. Karena itulah tidak mungkin akan tegak istana kehidupan Islam yang benar kecuali jika ditopang di atas tonggak pengakuan tauhid, karena ia adalah pengakuan yang sangat esensial bagi manusia untuk mewarnai kehidupannya, sesuai dengan kehendak Tuhan baginya.